Impact of ICRMP on the socio-economic status and participation of fishing households in Mati, Davao Oriental - Oracion, Enrique G.; Marcial, Dave E.; Alzate, Jessie V.; Dalagan, Roland A. (2013)
Employing quota sampling technique, 240 fishing households were interviewed in six sites along Mayo Bay (Dahican), Pujada Bay (Tamisan, Lawigan), and Balete Bay (Dawan, Mamali, Macambol) all in the City of Mati, Davao Oriental. These areas have established, or yet to be delineated as Marine Protected Areas (MPAs). Poverty incidence among households in all sited was high since their income fell below Php 7,000.00 per month. More men (64%) were engaged in agricultural enterprise than women. They had low (15.42%) participation in organizations which were engaged in coastal resource management. They Participated in decision-making processes that were relevant to coastal resource management but majority (59.96%) had less influence especially in policy making. Social facilities and services the households availed of included pre-school, elementary and high schools. Only few (10%) had collegiate education. Health centers were present in almost (92.92%) all sites. Safe sources of water were available in the form of communal faucets and public deep wells. Few (38.75%) availed of productive loans and financial assistance (25.42%) respectively. The distance of the respondents’ house from ICRMP interventions and enforcement landmarks were not significantly related to household income. Only household income and distance of fishing from MPA was significantly related. This means that those who fished near the MPAs were catching more due to “spill-over” effects (i.e., mature fish get out of the MPA and caught later by fishers). Thus, it was the direct utilization of fishery and marine resources that posed impact rather than the distance of their domicile.
Keywords: Marine Protected Areas; Integrated Coastal Resource Management Project; Mindanao studies; Fishing